2021
DOI: 10.1016/j.cub.2020.10.077
|View full text |Cite
|
Sign up to set email alerts
|

NO GAMETOPHORES 2 Is a Novel Regulator of the 2D to 3D Growth Transition in the Moss Physcomitrella patens

Abstract: Highlights d NO GAMETOPHORES 2 (PpNOG2) regulates the 2D to 3D growth transition in P. patens d PpNOG2 regulates gametophore initial cell formation and division plane orientation d PpNOG2 is required for the modulation of the auxin response d PpNOG2 acts upstream of CLAVATA and SCARECROW genes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 52 publications
(73 reference statements)
1
40
0
Order By: Relevance
“…5C). TheΔPpHCT lines phenocopied Δ PpCYP98 mutants(Renault et al, 2017) and newly reported PpHCT loss-of-function mutant Ppnog2-R(Moody et al, 2020), characterized by defective gametophore development (Fig. 5D-F, Fig.…”
mentioning
confidence: 70%
“…5C). TheΔPpHCT lines phenocopied Δ PpCYP98 mutants(Renault et al, 2017) and newly reported PpHCT loss-of-function mutant Ppnog2-R(Moody et al, 2020), characterized by defective gametophore development (Fig. 5D-F, Fig.…”
mentioning
confidence: 70%
“…The regulon comprises several genes encoding biosynthesis ( IPT3 Lindner et al, 2014), activation ( LOG Kuroha et al, 2009), degradation ( CKX Schwartzenberg et al, 2007), transport ( ENT , ABCG Borghi et al, 2015) perception ( CHK1 , CHK2 Schwartzenberg et al, 2016) and transduction ( ARR To and Kieber 2008) of cytokinins. In addition, the MYB circuit of the regulon also is predicted to induce cytokinin-responsive genes like NO GAMETOPHORES 2 ( NOG2 Moody et al, 2021), whose loss-of-function mutant similar to DEK1 also displays an overbudding phenotype. Consistently, the exogenous application of cytokinin (Schwartzenberg et al, 2007) and cytokinin-overproducing mutants (Schulz et al, 2000) also result in an overbudding phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the regulon also comprises essential components of the CLAVATA (CLV) peptide and receptor-like kinase pathway that has been shown to control cell fates and division planes of land plant apical stem cells (Fletcher et al, 1999; Whitewoods et al, 2018; Hirakawa et al, 2019) via CLV3/EMBRYO SURROUNDING REGION-Related (CLE Yamaguchi et al, 2016) peptide hormones which are perceived and transmitted to downstream signalling cascades via CLV1-type receptor-like kinases (Hazak and Hardtke 2016). Several studies in both Arabidopsis (Johnson et al, 2008) and Physcomitrella (Whitewoods et al, 2018; Moody et al, 2018; Moody et al, 2021) already have identified parallels in mutant phenotypes and expression patterns and have proposed models locating the CLV signalling pathway somewhere downstream of DEK1 and the moss APBs. The predicted overbudding-up regulon identified here, now provides us with a robust explanation for these connections.…”
Section: Resultsmentioning
confidence: 99%
“…Specification of the shoot initial cell requires both cytokinin and auxin (Ashton et al, 1978;Cove et al, 2006;Bennett et al, 2014). Factors including DEFECTIVE KERNEL 1 (DEK1), NO GAMETOPHORES 1 and 2 (NOG1 and 2) RECEPTOR-LIKE PROTEIN KINASE 2 (RPK2), and CLAVATA (CLV) function through APETALA2-type (AP2type) transcription factors to control the frequency of shoot initial cells (Aoyama et al, 2012;Perroud et al, 2014;Moody et al, 2018Moody et al, , 2021Whitewoods et al, 2018;Demko et al, 2021;Nemec Venza et al, 2021). In P. patens, a shoot initial cell undergoes several rounds of stereotypic, oblique cell divisions that lead to the formation of a tetrahedral shoot apical cell, marking the transition from a so-called 2D to 3D growth mode (Figure 2A; Harrison et al, 2009).…”
Section: Leaf Initiationmentioning
confidence: 99%
“…In P. patens, a shoot initial cell undergoes several rounds of stereotypic, oblique cell divisions that lead to the formation of a tetrahedral shoot apical cell, marking the transition from a so-called 2D to 3D growth mode (Figure 2A; Harrison et al, 2009). These divisions are also regulated by DEK1, CLV, NOG1, and NOG2 genes (Perroud et al, 2014;Moody et al, 2018Moody et al, , 2021Whitewoods et al, 2018;Nemec Venza et al, 2021), and precisely fulfilled by mitotic spindle orientation regulators, including microtubule-associated protein TARGETING FACTOR FOR Xklp2 and SABRE (Kosetsu et al, 2017;Kozgunova et al, 2020;Cheng and Bezanilla, 2021). Additionally, SOSEKI proteins might also be involved in apical cell identity specification and division (van Dop et al, 2020).…”
Section: Leaf Initiationmentioning
confidence: 99%